'Unfinished to perfection': Geoffrey Hill, revision, and the poetics of stone. Issue 7 (3rd July 2022) - Isaacs, David
ABSTRACT: In his early criticism, Geoffrey Hill conceives of the work of poetry as a process of strenuous revision towards a definable point of 'technical perfecti[on]', identifying the poet's ethical engagement in the end-directed 'act of self-critical decision'. The early poetry, contrastingly, expresses a distrust of the poem as finished product which is often manifest in a poetics of stone: a finished poem petrifies that which it attempts to remember. Employing a genetic methodology, this article tests whether these two conflicting attitudes might produce a friction that affects how the poems develop. It finds that the poems are animated by the question of how, ethically, to finish a poem and traces the vicissitudes of that animation in their developing deployment of stone imagery. Finally, it addresses the customary critical division between 'early' and 'late' Hill, arguing – through extended close attention to the notebook drafts of The Triumph of Love (1998) – that a dramatic shift in Hill's revisionary ethic catalyses a profound poetic change expressed in a reconception of stone as flux. Hill's new, late poetic seeks to comprise itself of its own revisionary processes, thus to remain perpetually in process and, in its unfinishedness, to manifest an ethical openness to alterity.